Theft under Islamic and Indonesian Criminal Law - Astutik, Zulfiani Ayu; Wibowo, Muhammad Rafif; Mulloh, Ahmad Fahmi Ilham; Diva, Adilla Putri (Universitas Muhammadiyah Yogyakarta, 2022)
Theft violates both legal and religious norms and it is a crime under Islamic and Indonesian Criminal Law . The study aims at comparing the regulation of theft both in Indonesia and in Islam. This normative legal research relies on secondary data and employs comparative approach. Comparison is made to explore the similarities and differences between Islamic criminal law and Indonesian criminal law with regard to theft especially on how this crime defined, the form of punishment , the requirement for imposing the punishments, and how effective are these punishment to deterring people from committing theft. The results of the study show that the use of imprisonment for theft as adopted in the Indonesian Penal Code seems to be ineffective for controlling theft cases. Hadd punishment as introduced in Islamic criminal law seems to be more promising for addressing the increasing number of theft cases. This is so because the application of cutting hand off not only prevents the thief to repeat the crime but also preventing others to do the same. Therefore, both special and general deterrence purposes are satisfied.